Soil CO2 Efflux in a Mixed Pine-Oak Forest in Valsaín (Central Spain) - Rosa Inclán; Daniel De la Torre; Marta Benito; Agustín Rubio (The Scientific World Journal)
Soil-surface CO2 efflux and its spatial and temporal variation were investigated in a southern Mediterranean, mixed pine-oak forest ecosystem on the northern slopes of the Sierra de Guadarrama in Spain from February 2006 to July 2006. Measurements of soil CO2 efflux, soil temperatures, and moisture were conducted in nine 1963-m2 sampling plots distributed in a gradient around the ecotone between Pinus sylvestris L. and Quercus pyrenaica Lam. forest stands. Total soil organic matter, Walkey-Black C, particulate organic matter, organic matter fraction below 53 μm, total soil nitrogen content, total soil organic carbon content, and pH were also measured under three representative mature oak, pine, and mixed pine-oak forest stands. Soil respiration showed a typical seasonal pattern with minimums in winter and summer, and maximums in spring, more pronounced in oak and oak-pine stands. Soil respiration values were highest in pine stands during winter and in oak stands during spring and summer.